2015
DOI: 10.1016/j.celrep.2015.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Retention of mRNA in Mammalian Tissues

Abstract: SummarymRNA is thought to predominantly reside in the cytoplasm, where it is translated and eventually degraded. Although nuclear retention of mRNA has a regulatory potential, it is considered extremely rare in mammals. Here, to explore the extent of mRNA retention in metabolic tissues, we combine deep sequencing of nuclear and cytoplasmic RNA fractions with single-molecule transcript imaging in mouse beta cells, liver, and gut. We identify a wide range of protein-coding genes for which the levels of spliced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
279
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(321 citation statements)
references
References 46 publications
39
279
2
1
Order By: Relevance
“…As is shown in Figure 11, we consider very broad ranges which cover 7 orders of magnitude -this encapsulates experimental estimates of nuclear export rates which are in the range 10 −4 to 10 1 min −1 (Bahar Halpern et al, 2015). Unsurprisingly, decreasing nuclear mRNA export (T 1 ) results in an increase in abundance of nuclear mRNA and increasing nuclear protein import (T 2 ) results in an increase in nuclear protein abundance.…”
Section: Appendix B: Dependence Of Variable Parameters On Transport Pmentioning
confidence: 97%
See 2 more Smart Citations
“…As is shown in Figure 11, we consider very broad ranges which cover 7 orders of magnitude -this encapsulates experimental estimates of nuclear export rates which are in the range 10 −4 to 10 1 min −1 (Bahar Halpern et al, 2015). Unsurprisingly, decreasing nuclear mRNA export (T 1 ) results in an increase in abundance of nuclear mRNA and increasing nuclear protein import (T 2 ) results in an increase in nuclear protein abundance.…”
Section: Appendix B: Dependence Of Variable Parameters On Transport Pmentioning
confidence: 97%
“…Additionally, from Figure 5 (b) and (d) we can see that there is an optimal import rate that minimises protein noise for mRNA export rates in the range 10 −3 to 10 1 min −1 . Interestingly, experimentalists have estimated the nuclear export rates to be in the range 10 −4 to 10 1 min −1 (Bahar Halpern et al, 2015), meaning that the import rate is crucial for determining whether or not noise is increased or decreased. By comparing the noise produced by model 3 vs. model 4 (plots (e) and (f)), we can see that the addition of negative feedback to a gene expression model with compartmentalisation can increase mRNA and protein noise if protein import is slow while if protein import is fast then the models produce approximately equal mRNA and protein noise levels.…”
Section: Compartmentalisation and Negative Feedback Can Increase Or Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the shape of the distributions of nuclear 175 transcript proportions was highly similar between tissues with slightly higher proportions estimated in this 176 study. These results suggest that the mechanisms regulating the spatial localization of these transcripts -for 177 example, rates of nuclear export and cytoplasmic degradation (Halpern et al 2015) -are conserved across 178 cell types.…”
mentioning
confidence: 92%
“…We compared our estimates of nuclear enrichment in cortex to mouse liver and pancreas based on data 173 from (Halpern et al 2015) and found moderately high correlation (r = 0.61) between 4,373 mostly house-…”
mentioning
confidence: 99%